A Mixed Methods Analysis of Global Mindset, Digital Skills, and Institutional Support on Digital Entrepreneurship Intentions - Rena Yuliana; Suryana Suryana; Suwatno Suwatno; Mokh Adib Sultan (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Digital entrepreneurship is becoming an attractive career for international students, yet empirical research on their entrepreneurial intentions in higher education remains limited. This study investigates the role of global mindset, digital skills, and institutional support in shaping the digital entrepreneurial intention of international students. This study uses a mixed methods approach with a sequential explanatory design, in which quantitative data is first collected through a survey of international students and analyzed using Partial Least Squares-Structural Equation Modelling (PLS-SEM). Subsequently, qualitative data were collected through semi-structured interviews and analyzed thematically to provide deeper insights into the quantitative findings. The results show that global mindset, digital skills, and institutional support have a positive and significant effect on digital entrepreneurship intention, with digital skills emerging as the strongest predictor. Further qualitative findings indicate that digital skills enhance students’ entrepreneurial self-confidence, while global mindset supports the recognition of opportunities in international markets. Institutional support is considered beneficial, although its effectiveness depends on how well it meets the specific needs of international students. These findings emphasise the importance of integrating individual competencies with institutional support in promoting digital entrepreneurship among international students.